The effect of deceptive advertising on consumption of the advertised good and its substitutes: The case of over-the-counter weight loss products - John H. Cawley; Rosemary J. Avery; Matthew Eisenberg (Institute for the Study of Labor (IZA), 2013)
This paper is the first to estimate the impact of exposure to deceptive advertising on consumption of the advertised product and its substitutes. We study the market for over-the-counter (OTC) weight-loss products, a market in which deceptive advertising is rampant and products are generally ineffective with potentially serious side effects. We control for the targeting of ads using indicator variables for each unique magazine read and television show watched. Our estimates indicate that exposure to deceptive advertising is associated with a lower probability that women, and a higher probability that men, consume OTC weight loss products. We find evidence of spillovers; exposure to deceptive print ads is associated with a higher probability of dieting and exercising for both men and women. We also find evidence that better-educated individuals are more sophisticated consumers of advertising and use it to make more health-promoting decisions.
Keywords: I1; I18; M37; M38; D83; 330; advertising; weight loss; obesity; deception; information; drugs; health